RAILWAY TRACKS VEGETATION IN RELATION TO VARIOUS MANAGEMENT, KUMAMOTO, JAPAN - Taizo Uchida; Masaaki Furuno; Hiroaki Furuno; Teruo Arase; Tetsuo Okano (GEOMATE Journal, 2025)
Research on the effects of different vegetation management regimes along railway tracks is valuable for effective train operation, security, and landscape conservation of the surrounding area. In addition, such surveys may offer important ecological insights into plant synanthropization and adventitivism. In this study, we conducted direct along-track surveys on the Minami-aso Railway after the 2016 Kumamoto Earthquake with special permission to clarify the effects of different management conditions on track vegetation and the ecological attributes of the species that make up the vegetation. The results suggested that the vegetation established along the tracks differs depending on the vegetation management regime that is employed in the region. Specifically, the use of herbicides was considered to reduce plant coverage, plant community height, and number of species (no/m2) on the tracks compared to management by physical removal of the vegetation. Furthermore, in addition to the use of herbicides, the percentage of plant coverage and the number of species per unit area were expected to be further reduced by the operation of the train. These differences in management status also had a significant effect on the composition of species that become established on the tracks (i.e., synanthropic species), but the effect of management regime on the ecological attributes of these species, such as the proportion of non-native species (adventization) and life forms defined by Raunkiaer (e.g., dormant) and Numata (e.g., dispersal types), was considered small.